Peran Sukuk Surat Berharga Syari’ah Negara (SBSN) Dalam Pertumbuhan Pembangunan Ekonomi Di Indonesia - Alfaatihah Intan Inayah; Fashola Khudin; Sumriyah Sumriyah (Lembaga Pengembangan Kinerja Dosen, 2023)
Indonesia has enormous potential in developing Islamic finance because Indonesia has the largest number of Muslims in the world and high economic growth. The issuance of State Sharia Securities (sukuk) has become the main financing instrument. The presence of sukuk further strengthens the government's ability to finance the budget deficit. The government has many choices in determining the combination of its financing instruments. The government can keep debt costs to a minimum. This study aims to determine 1) the development of sukuk in Indonesia and 2) the role of sukuk in Indonesia's economic growth. This research uses qualitative methods and library research approach. Researchers use secondary data, namely data sourced from existing literature or references. The results of this study are 1) The Indonesian government has issued Retail Sukuk (SR), namely SR 001 - SR 013. The issuance of State Sukuk from year to year continues to increase, in accordance with developments and strategies applied in the APBN. 2) The role of State Sukuk has a very positive impact, such as financing project development, encouraging development of the Islamic financial market, creating branch marks in the Islamic financial market, developing alternative investment instruments, and utilizing public funds.